Early Bowel Lengthening Procedures: Bi-Institutional Experience and Review of the Literature - Elisa Negri; Riccardo Coletta; Lynette Forsythe; Francesca Gigola; Maria Chiara Cianci; Antonino Morabito (MDPI AG, 2022)
Early bowel lengthening procedure (EBLP) has been defined as any bowel lengthening procedure performed before six months of age. The purpose of this paper is to compare our experience with literature on this subject to identify common indications. A bi-institutional retrospective analysis was performed. Diagnosis, type of surgery, age at procedure and outcomes were analysed. Eleven EBLP were performed in Manchester and Florence from 2006 to 2021. The median age at surgery was 126 days (102-180), pre-operative median short bowel (SB) length was 28 cm (17-49) with a post-operative median increase of 81%. Furthermore, a PubMed/Embase search was undertaken regarding bowel lengthening procedures performed in the last 40 years. Sixty-one EBLP were identified. The median age was 60 days (1-90). Serial transverse enteroplasty (STEP) was the most frequent procedure used, with a median increased bowel length of 57%. This study confirms that no clear consensus on indication or timing to perform early SB lengthening is reported. According to the gathered data, EBLP should be considered only in cases of actual necessity and performed in a qualified intestinal failure centre.